Decision Support System For Chicken Animal Feed Selection Using The Fuzzy Tsukamoto Method - Wahyuni, Sri; Furqan, Mhd.; Lubis, Aidil Halim (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
Selection of chicken feed is a fairly important decision support process. This decision support system was developed to assist breeders in choosing chicken feed based on predetermined criteria and alternatives. In this study using the Tsukamoto fuzzy method which produces a model of a system that can provide recommendations for choosing chicken feed that is applied in a decision support system. The Tsukamoto fuzzy method in determining the selection of chicken feed is based on 3 variables, namely price, quality and stock. Each variable consists of 3 sets which are combined in order to obtain 4 fuzzy rules, which are then used in the inference stage. The choice of chicken feed to be recommended (z) is searched by the centralized average defuzzification method. Testing will be carried out objectively where the decision support system is tested directly for capacity and filling out a questionnaire regarding satisfaction with the content of the point requirements and distributed to the owner of the animal feed shop. With this test, it can be seen that the features provided are easy to learn and easy to understand.